Design and Implementation of A Visible Light-Based Communications System - Caballero Barragan, Sebastian; Guerrero, Fabio G. (Ingeniería Solidaria, 2019)
Introduction: The publication is the product of the research “Prototipo de un sistema de telecomunicaciones basado en luz visible”, carried out at Universidad del Valle in 2018.Objective: The objective of this work was to build a functional prototype of a telecommunications system based on visible light through which the study of the most relevant characteristics, elements and behaviors in relation to this technology could be made.Methodology: To study the behavior of the developed prototype, different tests were performed varying some of the variables present in this type of telecommunications system. In addition, the developed prototype was tested in simplex and halfduplex modes.Conclusions: The results obtained when developing this work demonstrated the main characteristics of the prototype, its limitations, as well as the elements and variables that govern the most important aspects of its design.Originality: The presented design proposes the development of a low cost prototype, capable of obtaining the data to be sent through the connection to other devices through different communication peripherals or using the ADC present in the processing device used.Restrictions: Due to the reception elements used in the prototype there is a significant limitation on the maximum achievable transmission rate. In addition, it is important to mention that the conditions in which the prototype is deployed can affect its behavior, for example, elements that impede the line of sight between the telecommunications modules can stop the transmission.
Keywords: Visible Light Communications; Optical Wireless Communications; Optical Physical Layer; Manchester Coding; OOK Modulation